Bacterial Strain Diversity Within Wounds - Kirkup, Benjamin C. (Adv Wound Care (New Rochelle), 2015)
Significance: Rare bacterial taxa (taxa of low relative frequency) are numerous and ubiquitous in virtually any sample—including wound samples. In addition, even the high-frequency genera and species contain multiple strains. These strains, individually, are each only a small fraction of the total bacterial population. Against the view that wounds contain relatively few kinds of bacteria, this newly recognized diversity implies a relatively high rate of migration into the wound and the potential for diversification during infection. Understanding the biological and medical importance of these numerous taxa is an important new element of wound microbiology. Recent Advances: Only recently have these numerous strains been discovered; the technology to detect, identify, and characterize them is still in its infancy. Multiple strains of both gram-negative and gram-positive bacteria have been found in a single wound. In the few cases studied, the distribution of the bacteria suggests microhabitats and biological interactions. Critical Issues: The distribution of the strains, their phenotypic diversity, and their interactions are still largely uncharacterized. The technologies to investigate this level of genomic detail are still developing and have not been largely deployed to investigate wounds. Future Directions: As advanced metagenomics, single-cell genomics, and advanced microscopy develop, the study of wound microbiology will better address the complex interplay of numerous individually rare strains with both the host and each other.